ANALISA MATERI PELAJARAN SEJARAH KEBUDAYAAN ISLAM MADRASAH ALIYAH KELAS XI DAN RELEVANSINYA DI INDONESIA - Siti Masulah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2018)
One part of the subjects of national education is Islamic education. As for the grouping of Islamic teachings in the form of subjects in Madrasah ranging from Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTs), and Madrasah Aliyah (MA), there are subjects devoted to religious specialization. At the level of Madrasah Aliyah (MA), the specialization of the Religious sciences was developed in the form of study-specific subjects and there were also subjects that served as supporters such as the subjects of Islamic Cultural History. In this paper, the author analyzes the student manual for the subjects of Islamic Culture History class XI (Scientific Approach Curriculum 2013) using an analytical study approach in terms of the order of subject matter in the book and the double movement hermeneutics study approach ala Fazlur Rahman. The results of this study explain that the SKI subjects have been elaborated with clear and detailed indicators, but the subject matter of the SKI has not provided an analysis description for the development of scientific insights of students in answering the actual problems, for example, the plurality that characterizes the Indonesian nation. Therefore, the SKI study must involve Fazlur Rahman's hermeneutic analysis and Nietzsche's critical history analysis to read past phenomena to build on current progress in accordance with the mandate of National Education System Law No. 20 of 2003.